A Theoretical Pore Network Model for the Soil–Water Characteristic Curve and Hysteresis in Unsaturated Soils - Gómez, Angela V. (Civil Engineering Journal, 2025)
This study presents a novel approach to modeling the soil–water characteristic curve in unsaturated soils, employing Monte Carlo simulations to capture the complex behavior of the pore network. The primary objective is to develop an alternative method to represent the hysteretic nature of the soil–water characteristic curve, which is critical for understanding unsaturated soil behavior in various engineering applications. The proposed approach conceptualizes soil as a network of interconnected pores, where each pore interacts with its nearest neighbors. Monte Carlo simulations are used to model the pore-filling distribution as a function of pressure differences during drying and wetting cycles. The model effectively reproduces the characteristic hysteresis curves associated with the hydraulic and mechanical processes in unsaturated soils. A key finding is that the simulated soil–water characteristic curve captures the impact of pore-scale interactions and reflects the complex hysteresis effects observed in experimental data. The novelty of this work lies in integrating pore network modeling with Monte Carlo simulations, addressing limitations of traditional models and offering a more accurate representation of unsaturated soil behavior. While the model has not yet undergone experimental validation, it provides valuable insights into the dynamics of soil moisture retention and serves as a foundation for future experimental testing and refinement of soil–water models. Doi: 10.28991/CEJ-2025-011-02-021 Full Text: PDF